2018
DOI: 10.1111/anec.12604
|View full text |Cite
|
Sign up to set email alerts
|

Combining noninvasive risk stratification parameters improves the prediction of mortality and appropriate ICD shocks

Abstract: Background: Sudden cardiac death (SCD) results from a complex interplay of abnormalities in autonomic function, myocardial substrate and vulnerability. We studied whether a combination of noninvasive risk stratification tests reflecting these key players could improve risk stratification. Methods:Patients implanted with an ICD in whom 24-hr holter recordings were available prior to implant were included. QRS fragmentation (fQRS) was selected as measure of myocardial substrate and a high ventricular premature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A potential Holter-based parameter is beat-to-beat variability of repolarisation that shows promise of translation to ICD monitoring [33][34][35]. Repolarisation parameters derived from standard 12-lead electrocardiogram (ECG) analysis include QT-interval and its dispersion, T-peak to T-end and microvolt T-wave alternans, which may reflect the dynamic substrate for arrhythmias as well as depolarisation, and parameters such as QRS duration and QRS fragmentation that reflect conduction abnormalities [36,37]. These new parameters still need to be assessed comprehensively before recommendation to clinical practice [38].…”
Section: Current Management: Much To Be Desired From Pharmacotherapymentioning
confidence: 99%
“…A potential Holter-based parameter is beat-to-beat variability of repolarisation that shows promise of translation to ICD monitoring [33][34][35]. Repolarisation parameters derived from standard 12-lead electrocardiogram (ECG) analysis include QT-interval and its dispersion, T-peak to T-end and microvolt T-wave alternans, which may reflect the dynamic substrate for arrhythmias as well as depolarisation, and parameters such as QRS duration and QRS fragmentation that reflect conduction abnormalities [36,37]. These new parameters still need to be assessed comprehensively before recommendation to clinical practice [38].…”
Section: Current Management: Much To Be Desired From Pharmacotherapymentioning
confidence: 99%
“…If it is noticed before replacement however, we would currently still consider the patient for replacement despite their improved prognosis because other studies showed that the incidence of appropriate shocks, hence the arrhythmic risk, remains clinically important (Schliamser et al, 2013;Vandenberk et al, 2017;Zhang et al, 2015 We believe our results show promise for developing a practical algorithm of repeated risk stratification to guide the decision on when and whether or not a patient should receive a first ICD implantation or ICD replacement. Combining noninvasive risk stratification tests according to their physiological background and their predictive value, based on optimal sensitivity and/or specificity can improve the risk prediction of SCD and mortality (Exner et al, 2007;Vandenberk et al, 2019). Of course, this should be tested in a prospective trial comparing it with current guidelines and determine whether it could expand ICD indications beyond LVEF or minimize implants in patients with a high nonarrhythmic mortality risk and low arrhythmic risk.…”
Section: Hrtmentioning
confidence: 99%